Bilişsel Ahlak Gelişimi Kuramı: Kohlberg ve Sonrası - (:unkn) unknown (My University, 2006)
Ahlak gelişimi konusunda en etkili ve en fazla araştırma yapılan kuram olarak Kohlbergçi Bilişsel-Gelişimsel Kurama yöneltilen temel eleştiriler ve Yeni Kohlberçilerin (Neo- Kohlbergian) şu anki bakış açılan, bu derleme çalışmasının konusudur. Öncelikle Kohlberg'in kuramı çok kısa özetlenmiş ve Gilligan (Cinsiyet Farklılıkları) ve Truel'in (Alan Teorisi) yönelttikleri detaylı eleştiriler üzerinde durulmuştur. Türkiye'de yapılan alan çalışmalarının bulgularına da yer veren çalışma Rest ve arkadaşlannm kuramla ilgili değerlendirmeleri ve açılımlanyla sona ermiştir.

The topic of the present compilation study is basic criticism directed at Kohlbergian Cognitive- Developmental Theory, the most influential and most-researched theory on moral development, as well as the latest perspectives of the Neo-Kohlbergians. First, the theory was summarized briefly. Then critics were taken into account with a special emphasis on Gilligan's (Gender Differences) and Truel's (Domain Theory). The empiric studies conducted in Turkey were interspersed throughout the text and the study was finalized with the Rest and colleague's new approaches and expansions to the theory.
Keywords: Eğitim, Eğitim Araştırmaları